3D MODELLING AND TEMPERATURE DISTRIBUTION SIMULATION OF PORTABLE INCUBATOR CHAMBER WITH PASSIVE HEAT SOURCE - PHASE CHANGE MATERIAL (PCM) : PARAFFIN - Putri Ismu Chumairoh, Amanda
The data from Profil Kesehatan Indonesia showed the death of baby neonatal has significantly decreased and most of the death happened in Daerah Tertinggal, Perbatasan dan Kepulauan (DTPK) This case happened because DTPK is the islands area with limited health access that rely on center hospital that located so far from one island to another so it will takes time for a newborn baby that needed incubator to transport and get a treatment in proper hospital. So in this final project will be discussed the development aspect of portable incubator specification as solution of alternative media that helped the newborn baby to transport within his area into the center hospital. This portable incubator is needed because baby's body can't perfectly regulate it's body temperature so it needed thermal support system from the outside. The prototype of incubator portable has been made before with phase change material PCM : Paraffin as passive heat system to warm the air inside incubator. That paraffin material generate heat by the latent of heat that stored after paraffin material getting boiled and then released the heat inside incubator. In this final project will be developed the portable incubator by heat transfer modelling and simulation in Comsol Multiphysics program to minimalize experimental cost repetition for Phase Change Material (PCM) : Paraffin trial. So from the modelling and simulation method the portable incubator has the output about the suggestion of thermal engineering aspect based on the prototype system before. From this research, it has been identified the thermal characteristic about paraffin material as PCM with ????????,????????????????????????=3.75 ????????????/?????, ????=34.43 ????????????/????, and ????????,????????????????????=3.23 ????????????/?????. From modelling and simulation method it has been identified the suggestion for the thermal system with PCM latent of energy 55 W/m2 with surface temperature of simulation 36.4? and chamber incubator temperature 32.69? from 48.1 g material of paraffin.